2019
DOI: 10.1016/j.virusres.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of anisomycin against spring viraemia of carp virus in epithelioma papulosum cyprini cells and zebrafish

Abstract: A B S T R A C T Spring viraemia of carp (SVC) caused by spring viraemia of carp virus (SVCV) is an acute and highly lethal viral disease of cyprinid fish. However, effective therapy for SVC is still scarce until now. Here we evaluated the inhibition of anisomycin (Ani), a metabolite produced by Streptomyces griseolus, on the replication of SVCV in vitro and in vivo. Our results demonstrated that Ani could suppress SVCV replication with the maximum inhibitory rate > 95% in epithelioma papulosum cyprini (EPC) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Traumatic hippocampal neurons in the vehicle group were treated with DMSO (TET vehicle). To determine whether the effect of TET on traumatic hippocampal neurons was related to the IRE1α/JNK/CHOP signal pathway, traumatic hippocampal neurons in the Anisomycin group and the TET + Anisomycin group were treated with 10 nM Anisomycin for 24 h (Shen et al., 2019 ), and traumatic hippocampal neurons in the TET + Anisomycin group were treated with TET for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Traumatic hippocampal neurons in the vehicle group were treated with DMSO (TET vehicle). To determine whether the effect of TET on traumatic hippocampal neurons was related to the IRE1α/JNK/CHOP signal pathway, traumatic hippocampal neurons in the Anisomycin group and the TET + Anisomycin group were treated with 10 nM Anisomycin for 24 h (Shen et al., 2019 ), and traumatic hippocampal neurons in the TET + Anisomycin group were treated with TET for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of marine actinobacteria, the potential of Streptomyces strains isolated from sponges revealed the improved growth of an ornamental fish (Xiphophorus hellerii) [56], and the administration of Streptomyces as single cell protein resulted in improved growth of the ornamental fish Southern platy fish (Xiphophorus maculatus) [36]. The potential of Streptomyces as a probiotic in aquaculture was reviewed by Tan et al [9], and to avoid overlaps, only studies published post-2016 and studies not reported in the review of Tan et al [9] are discussed in this section.…”
Section: Actinobacteria As Probioticsmentioning
confidence: 99%
“…with the virus to zebrafish, significantly increasing the survival of the infected fish and reducing the viral load (Shen et al . 2019).…”
Section: Pharmacological Drugs Directed To Different Steps Of the Vir...mentioning
confidence: 99%
“…This compound showed antiviral activity against SVCV in EPC cells but also in vivo effects when it was administered i.p. with the virus to zebrafish, significantly increasing the survival of the infected fish and reducing the viral load (Shen et al 2019).…”
Section: Protein Synthesis Post-translational Modifications Virion As...mentioning
confidence: 99%